2014
DOI: 10.11138/ccmbm/2014.11.1.077
|View full text |Cite
|
Sign up to set email alerts
|

Strontium ranelate improves delayed healing of osteolytic lesions of the jaw in a man with chronic osteomyelitis. Case report

Abstract: SummaryWe report the case of a man with osteolytic lesions of the right mandible due to chronic osteomyelitis, with delayed healing after six months of antibiotic therapy. The patient received off-label therapy with strontium ranelate, with significant radiological improvement of his condition after 3 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
(31 reference statements)
1
2
0
Order By: Relevance
“…Congruently, bone cellular alterations related to SrRan treatment within the defect are in agreement with previous findings in growing animals: SrRan treatment was associated to a positive bone balance with plausible increased bone formation [25,26]. Despite no human available data about SrRan effects during growth, Stathopoulos et al [36] have shown in a case report that SrRan improves delayed healing of osteolytic lesions of the jaw by a decreased osteoclastic activity as well as potential enhancement of osteoblastogenesis.…”
Section: Discussionsupporting
confidence: 90%
“…Congruently, bone cellular alterations related to SrRan treatment within the defect are in agreement with previous findings in growing animals: SrRan treatment was associated to a positive bone balance with plausible increased bone formation [25,26]. Despite no human available data about SrRan effects during growth, Stathopoulos et al [36] have shown in a case report that SrRan improves delayed healing of osteolytic lesions of the jaw by a decreased osteoclastic activity as well as potential enhancement of osteoblastogenesis.…”
Section: Discussionsupporting
confidence: 90%
“…[17][18][19][20][21][22] Strontium ranelate also improves fracture healing in humans 23 and is recommended as an off-label therapy for delayed and complicated healing of bone lesions. 24,25 Nevertheless, the effect of strontium ranelate on tooth extraction wound healing has not been evaluated up to now. Hence, the purpose of this study was to assess the effects of strontium ranelate on tooth-extraction wound healing of rats with estrogen deficiency and sufficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In general, pre‐clinical evidence indicates that strontium ranelate therapy improves bone healing in fractures and in surgically created bone defects, especially under conditions of estrogen deficiency 17–22 . Strontium ranelate also improves fracture healing in humans 23 and is recommended as an off‐label therapy for delayed and complicated healing of bone lesions 24,25 . Nevertheless, the effect of strontium ranelate on tooth extraction wound healing has not been evaluated up to now.…”
Section: Introductionmentioning
confidence: 99%